Financial documents of Komsomol organizations as the source of Komsomol history in 1960s - E. V. Kamaeva (Омский научный вестник: Серия "Общество. История. Современность")
The article analyzes the informational potential of financial documents of Komsomol organizations, introduced into scientific circulation for the first time. The source base for the study is composed of documents from the financial departments of Komsomol organizations deposited in the funds of the Russian State Archive of Socio-Political History, the State Archive of the Republic of Tatarstan and the State Archive of Contemporary History of the Ulyanovsk Region. The purpose of the article is to analyze a wide range of financial documents and determine their historical worth when studying the history of the Komsomol in the 1960s. The financial and economic department of the administration of the Central Committee of the AllUnion Leninist Young Communist League was engaged in the preparation of the budget for the Komsomol organization and the distribution of funds for grassroots committees. The analysis of financial documents of the Komsomol makes it possible to trace the sources of funds in the conditions of the termination of state subsidies in the 1960s and highlight the priority areas of work of the Komsomol. The documents of the regional Komsomol organizations reflect the material condition and financial support of grassroots committees. The author notes a certain complexity of the classification of financial documents in modern source criticism literature. The author proposes the use of the term «financial and reporting documentation», which includes the budget, financial statements, balance sheets, distribution of funds by budget items. This material may be of scientific interest in the study of certain periods and directions in the history of the Komsomol.